(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The framers of the Indian Constitution sought to establish India as a democratic republic country. At the same time, it has also emphasized preserving secularism as the base of its democratic structure. The word secularism was added to the Indian constitution by the 42nd Amendment, 1976, and it is also a part of the basic structure of the Indian constitution. India, being a land of diversity in terms of language, culture, religion, etc., at many instances faces challenges that pose a threat to the societal fabric of India. At many times, questions have been raised about the need and practice of secular ideas in India. However, it is the secular values imprinted in the life and constitution of India that bind the people against common threats. In this paper, an attempt will be made to outline the nature and characteristics of the secular structure of India, the Indian notion of secularism, as well as the challenges faced by secularism over the years.